Теоретичні передумови розвитку та застосування екосоціального підходу в інтродукційних дослідженнях - Sliusar, S.I.; Kuznetsov, S.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
The expediency of application of the ecosocial approach was based for further development of methodology of introduction’s investigations. Necessity of research of any introductional plant must be on level of any introductional individual, deme, population or culturecenosis as the com – ponent part of indivisible ecosocial environment. This con nects with action on alive organism of complex combined of nature and social factors.